Lichens of the Hassan Tower Monument (Rabat, Morocco) (Atlas Journal of Biology, 2017)
This paper describes the lichen species that colonize the walls of the Hassan Tower, a historical monument of Morocco. The lichen species identified as Caloplaca flavescens, C. Vitellinula, Rocella phycopsis and Xanthoria calcicola are distributed differently on the walls of the tower. In addition to other environmental factors, such lichen species encountered are involved in one way or another in the deterioration of building materials of the Hassan Tower.